'Body on the Wire': Leontia Flynn on Living through Divided Politics. Issue 2 (November 2020) - Obert, Julia C.
Abstract : Although Northern Irish poet Leontia Flynn's work has always been politically invested, her 2018 collection The Radio shifts its gaze from global pressures on the local to local lessons for global geopolitics. The poet of 'the new North', born and raised amidst sectarian fervour, can offer all of us a political survival strategy for bearing the weight of our deeply divided world. Despite the polarizing pull of Trump and Brexit, we must, Flynn suggests, resist the lure of extremism, and must instead cultivate a sense of lively betweenness – a position exemplified by the 'body on the wire' that appears in The Radio's 'First Dialogue'. This tightrope walker is far from inert; she is rather paused, vibrating, perched energetically between two points. She therefore exemplifies the volume's broader conviction that we must be willing to hold ideas in tension and to dwell deeply with that tension – to find ways of remaining dynamic in the face of the deadening forces of dogmatism.